Use of recycled materials in floating stone columns. Issue 2 (8th April 2019) - Shahverdi, Mohsen; Haddad, Abdolhosein
Abstract : In the presented research, in order to improve the bearing capacity of a soft clay bed, the performance of floating stone columns constructed of recycled aggregates from demolition waste was investigated. For this purpose, a single stone column with three types of materials, including recycled crushed brick, recycled crushed concrete, and gravel as natural aggregate was modeled. Furthermore, the quality of recycled aggregates used was evaluated by aggregate index tests such as aggregate crushing value and aggregate impact value. The results of the recycled aggregate index tests demonstrated a poorer performance of these materials compared to the natural aggregate. Despite this, the bearing capacity of the clay bed reinforced with the floating column which was filled with crushed brick or crushed concrete was approximately five times the bearing capacity of the unreinforced clay bed. Moreover, the loading results showed that the floating stone columns constructed of a type of aggregate delivered a better performance in comparison to the columns constructed of a combination of several types of recycled aggregates together or a combination of natural and recycled aggregates.